A compact and stable diagnostic system for major species concentration and temperature in the combustion flow field by Raman scattering - Wang, Ke; Zhang, Zhenrong; Wang, Sheng; Wang, Yamin; Liu, Yangyang; Wu, Haolong; Shao, Jun; Ye, Jingfeng; Cai, Jianghuai (Frontiers in Physics, 2025)
A compact and stable diagnostic system is established using Raman scattering to measure parameters such as major species concentration and temperature in the combustion flow field. Despite an engine’s huge vibration, the prototype works stably and has an uncertainty level below 5%. A standard Hencken burner validates the results. From our perspective, the prototype represents a novel practical application of mature Raman spectroscopy technology, warranting interaction with engineering experts in relevant fields. The background and signal are distinguished with the half-wave plate. The orthogonality and angle between excitation and signal contribute to a good signal-to-noise ratio (SNR). The compactness of the device is fully considered. The device exhibits good resistance to adverse environments. The system’s temperature is minimally affected by external conditions, and it has good vibration resistance features. The temporal resolution of a single pulse of the device is 10 ns. The spatial resolution is 3 mm × 0.2 mm × 0.2 mm with one-dimension measurement available.